THE LINGUISTIC REPERTOIRE OF A YOUNG ADULT, AND A MIDDLE ADULT OF A NGAJU DAYAKNESE FAMILY IN CENTRAL KALIMANTAN - Kesy Kesetiaan; Henny P.S. Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study is a qualitative study about linguistic repertoire and the subjects are three people from three different ages of a Ngaju Dayaknese family consisting of the mother, the first child and the third child. This study was conducted in order to see the linguistic repertoire of them. In order to reach the research objectives, I used the theories of linguistic repertoire by Milroy and Milroy (1990) and code choice by Holmes (2001). From my study, I found that the linguistic repertoire of the third child is Banjarese language, Indonesian language, and Ngaju Dayaknese language, the linguistic repertoire of the first child is Ngaju Dayaknese language, Indonesian language, and Banjarese language, and the linguistic repertoire of the mother is Ngaju Dayaknese language, Banjarese language, and Indonesian language. It can be concluded that the linguistic repertoire of each subject can be distinguished one from another and it was influenced by the environment he/she was exposed to.